Relationship Changes Between Parents and Children of Modern Family During Covid-19 Pandemic in Hukurila, South Leitimur District, Ambon City - Feky Manuputty; Simona Christina Henderika Litaay; Prapti Murwani; Rizki Muhammad Ramdhan (Ridwan Institute, 2022)
The nuclear family has an important meaning in modern society. In Hukurila, South Leitimur District, Ambon City, generally families live a modern lifestyle, in which the relationships between parents and children are no longer carried out properly. This can be seen from the reduced parental supervision of their children at home. Parents are busy with various activities and conversely the children are also busy with their own activities. The aim of this research is to find out and explain the forms of changes in the relationship between parents and children in modern families during the COVID-19 pandemic. The method used is a qualitative research method by means of in-depth interviews and observations and uses secondary and primary data sources. This study found changes in the relationship between parents and children, namely the reduced parental supervision of children, the more distant the relationship between parents and children due to the social environment and millennial subculture and parents are seen as passing on only a few values ??of life to their children.